Words in motion: Motor-language coupling in Parkinson's disease - García, Adolfo Martín (2014)
A growing body of evidence indicates that neurodegenerative motor disorders involved high-order cognitive dysfunctions. Crucially, evidence obtained in multiple behavioral, neuroimaging, and electrophysiological studies points to selective impairments of action language -that is, processing of linguistic stimuli denoting motor actions, including idioms (e.g., cut a rug) and action verbs (e.g., clap). Action-verb deficits (with relative preservation of noun processing) have been repeatedly documented in Parkinson's disease (PD). However, research on relevant biomarkers is still scant, and clinical implications of these findings have not yet been formally discussed. Relevant insights may be obtained through the assessment of motor-language coupling (i.e., the behavioral and neural integration of action-verb processing and ongoing motor actions). We propose that motorlanguage coupling deficits, as indexed by a cortical-subcortical network, may constitute an early neurocognitive marker of PD. Specifically, deficits in this domain at the prodromal stage may be detected through the actionsentence compatibility (ACE) paradigm, which induces a contextual coupling of ongoing motor actions and action-verb processing. Our translational proposal is supported and illustrated by recent studies demonstrating the sensitivity of the ACE technique as well as its potential to assist in differential diagnosis and interventionprogram design.